Trauma-spectrum symptoms among the Italian general population in the time of the COVID-19 outbreak. Issue 1 (1st January 2021) - Rossi, Rodolfo; Socci, Valentina; Talevi, Dalila; Niolu, Cinzia; Pacitti, Francesca; Di Marco, Antinisca; Rossi, Alessandro; Siracusano, Alberto; Di Lorenzo, Giorgio; Olff, Miranda
ABSTRACT: Background : Recent evidence showed adverse mental health outcomes associated with the COVID-19 pandemic, including trauma-related symptoms. The Global Psychotrauma Screen (GPS) is a brief instrument designed to assess a broad range of trauma-related symptoms with no available validation in the Italian population. Aims : This study aimed to examine the factor structure of the Italian version of the GPS in a general population sample exposed to the COVID-19 pandemic and to evaluate trauma-related symptoms in the context of COVID-19 related risk factors associated with lockdown measures. Methods : We conducted a cross-sectional web-based observational study as part of a long-term monitoring programme of mental health outcomes in the general population. Eighteen thousand one hundred forty-seven participants completed a self-report online questionnaire to collect key demographic data and evaluate trauma-related symptoms using the GPS, PHQ-9, GAD-7, ISI, and PSS. Validation analyses included both exploratory and confirmatory factor analysis and correlation analyses. The relation with putative COVID-19 related risk factors was explored by multivariate regression analysis. Results : Exploratory factor analyses supported a two-factor model. Confirmatory factor analysis showed that the best fitting model was a three-factor solution, with core Post-traumatic Stress Symptoms (PTSS) (re-experiencing, avoidance, hyperarousal), Negative Affect (symptoms of depressed mood, anxiety, irritability), and Dissociative symptoms. GPS Risk factors and specific COVID-19 related stressful events were associated with GPS total and the three factor scores. Conclusions : Our data suggest that a wide range of trauma-spectrum symptoms were reported by a large Italian sample during the COVID-19 pandemic. The GPS symptoms clustered best in three factors: Negative Affect symptoms, Core PTSS, and Dissociative symptoms. In particular, high rates of core PTSS and negative affect symptoms were associated with the COVID-19 pandemic in Italy and should be routinely assessed in clinical practice. Abstract : HIGHLIGHTS: This study examines the factor structure of the Global Psychotrauma Screen. Data were collected during the first COVID-19 lockdown in Italy. A three-factor model was the best solution. Core Post-Traumatic and Negative Affect symptoms were associated with the COVID-19 pandemic.